PENGARUH STANDAR AKUNTANSI KEUANGAN INDONESIA BARU, UKURAN KANTOR AKUNTAN PUBLIK, UKURAN PERUSAHAAN DAN UMUR PERUSAHAAN TERHADAP AUDIT REPORT LAG - Novita Jayanti Sitorus; Aloysia Yanti Ardiati (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2017)
This study aims to determine the effect of New SAK, KAP size, firm size and age of the company to Audit Report Lag. Research data is secondary data obtained by downloading data of financial statements of manufacturing companies listed in Indonesia Stock Exchange in the period 2011-2014 through the official website BEI www.idx.ac.id. The analysis tool used is multiple regression analysis.The results show that New SAK and firm size have no effect on Audit Report Lag. Whereas, firm size and age has significant influence on Audit Report Lag.Keywords: New SAK, KAP Size, Company Size, Company Age, Audit Report Lag.